Censorship or Profit? The Manipulation of Dialogue in Dubbed Youth Films - Zanotti, Serenella (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Youth films are a field of special interest to AVT scholars due to the genre’s propensity for potentially disturbing content, both thematic and linguistic. In youth films the depiction of teenage sexuality, violence, crime and drug consumption often combines with strong language. Both represent problematic areas for the dubbing translators, who often act as censorial agents under the pressure of a number of factors, including target cultural norms and values as well as local regulations. Existing work on censorship in AVT has showed that potentially disturbing elements tend to be toned down, if not censored, in dubbed films. Based on both textual analysis and archival research, this study provides further evidence to previous research, while also showing the role of distribution companies in deciding the level of manipulation imposed on the film dialogue.